The course of prosthodontic patients' oral health-related quality of life over a period of 2 years. Issue 2 (February 2015) - Aarabi, Ghazal; John, Mike T.; Schierz, Oliver; Heydecke, Guido; Reissmann, Daniel R.
Abstract Objectives Treatment effects should be large and long-lasting. The aim of this study was to describe for patients treated with fixed dental prostheses (FDP), removable dental prostheses (RDP), and complete dentures (CD) how they perceived their oral health over a period of two years using the concept oral health-related quality of life (OHRQoL). Methods In this prospective clinical study, a consecutive sample of 272 adult patients receiving prosthodontic treatment was recruited. The Oral Health Impact Profile (OHIP-G) was used at baseline before prosthodontic treatment, 4–6 weeks, and 6, 12, 18, and 24 months after therapy. The OHRQoL of the prosthodontic patients were compared with findings from a general population-based study (N = 811), and OHRQoL changes were compared to the minimal important difference of the OHIP. Results At baseline, mean OHIP sum score was 31.1 points, indicating substantially lower OHRQoL than for general population subjects. After a substantial treatment-induced drop of OHRQoL impairment in all treatment groups, OHIP scores increased slowly, but did not reach pretreatment levels after 24 months. While full treatment effect was already present 4–6 weeks after treatment in the FDP and RDP groups, OHRQoL improvement continued until the 12-month assessment in the CD group. When follow-up OHIP scores of the entire sample were compared to baseline scores, all changes were statistically significant, but the magnitude exceeded the OHIP's MID (6 points) only in the assessments at 4–6 weeks, 6 months, and 12 months. Conclusion Effects of prosthodontic interventions on patients' perception seem to last for at least 2 years. Clinical significance Taking into consideration that prosthodontic treatment is only one factor for the oral health of a patient, prosthodontic rehabilitation seems to have a substantial influence on a patient's oral health trajectory.